Divergence of feminine and masculine worlds in prose texts by Olga Tokarczuk and Edmund Hlatky - Mitka, Marek (Wydawnictwo Uniwersytetu Rzeszowskiego, 2024)
In the present study, the author focuses on the interpretation of prose texts by the Polish author Olga Tokarczuk and the Slovak writer Edmund Hlatky. He finds a high degree of thematic-motivic congruence between their texts, which is related to the depiction of divergences between the character of the so-called feminine and masculine worlds. The author’s main focus in the study is on the detailed portrayal of the characters and the specifics of their interaction with the world around them. In the case of Olga Tokarczuk, he focuses on the prose books House of Day, house of Night and Playing on Many Drums, and in the case of Edmund Hlatky on his short story collections Autumnal Haze and Glory and Mystery. The author observes the psychology of the heroes in life’s exposed moments and trials, examines the degree to which the use of religious motifs and the Bible is functional, and analyses the degree of tragedy that weighs on the heroes in their different psychological states and in their search for the meaning of life. The author finds a high degree of similarity in the portrayal of the female characters in the two interpreted novelists, which can be seen from the aspect of biblical heroism, redemption or at least from the aspect of peaceful loving asylum, which stands in contrast to the male characters.

W niniejszym opracowaniu autor skupia się na interpretacji tekstów prozatorskich polskiej pisarki Olgi Tokarczuk i słowackiego pisarza Edmunda Hlatky‘ego. Stwierdza wysoki stopień zbieżności tematyczno-motywacyjnej między ich tekstami, co wiąże się z przedstawieniem rozbieżności między charakterem tzw. świata kobiecego i męskiego. W badaniu autor skupia się przede wszystkim na szczegółowym portretowaniu postaci i specyfice ich interakcji z otaczającym światem. W przypadku Olgi Tokarczuk koncentruje się na jej książkach Dom dzienny, dom nocny i Gra na wielu bębenkach, a w przypadku Edmunda Hlatky‘ego na jego zbiorach opowiadań Jesenný opar (Jesienna mgła) oraz Sláva a tajomstvo (Sława i tajemnica). Autor śledzi psychologię bohaterów w ich najważniejszych momentach i próbach, bada, w jakim stopniu wykorzystanie motywów religijnych i Biblii jest funkcjonalne, a także analizuje stopień tragizmu, który ciąży na bohaterach w ich różnych stanach psychicznych i poszukiwaniach sensu życia. Autor odnajduje wysoki stopień podobieństwa w przedstawianiu postaci kobiecych w dziełach obojga interpretowanych pisarzy, które można postrzegać przez pryzmat biblijnego heroizmu, odkupienia lub przynajmniej w intencjach spokojnego, życzliwego azylu. Co ważniejsze, wszystkie te aspekty kontrastują z charakterem męskiego świata, przedstawionego w tekstach obojga analizowanych pisarzy.
Rozbieżność świata kobiecego i męskiego w tekstach prozatorskich Olgi Tokarczuk i Edmunda Hlatky’ego
Keywords: Edmund Hlatky; literary comparatistics; interpretation of a fictional text; feminine world; fragmentarization; metaphysics; psychology of the subject; communication aesthetics; Olga Tokarczuk; komparatystyka literacka; interpretacja tekstu artystycznego; świat kobiecy; fragmentaryzacja; metafizyka; psychologia podmiotu; estetyka komunikacji